Field reports, Randall Pinkston, fall 1990 - Pinkston, Randallet al (1990)
Field reports in the form of a note and four checklists submitted by Randall Pinkston with two other observers for fall 1990. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1990. Epson - sheet feed